2017
DOI: 10.15405/epsbs.2017.12.47
|View full text |Cite
|
Sign up to set email alerts
|

Do Cognitive Styles Affect Psychophysical Tasks Performance?

Abstract: Background. In order to deepen understanding of signal detection/discrimination processes we have to focus on highlighting individual differences in observers' sensory performance due to the contribution of various variables of personality and cognition spheres. The purpose of our study was to test cognitive style factors (augmenting-reducing, levelling-sharpening, flexibility-rigidity of cognitive control, equivalence range, and focusing-scanning) influencing performance of psychophysical tasks.Methods. Ninet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Our previous study showed that these CS dimensions relate to higher accuracy of solving signal detection tasks, i.e. higher sensory sensitivity, due to their specific features in contrast to opposite dimensions of corresponding CS (Volkova & Gusev, 2017). In particular, they have an advantage in sensitivity due to their ability to: (1)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed that these CS dimensions relate to higher accuracy of solving signal detection tasks, i.e. higher sensory sensitivity, due to their specific features in contrast to opposite dimensions of corresponding CS (Volkova & Gusev, 2017). In particular, they have an advantage in sensitivity due to their ability to: (1)…”
Section: Resultsmentioning
confidence: 99%
“…The experimental session started with two psychophysical tasks, each of which had two difficulty levels (easy and hard): (1) visual signal detection 'yes-no' (YN) task, where a distractor was added to the original procedure, and (2) 'same-different' loudness signal discrimination (SD) task. A detailed description of the tasks, including stimuli, instructions, software and apparatus, is presented in our previous paper (Volkova & Gusev, 2017). We assessed sensory sensitivity (A′), strictness of criterion index (YesRate), RT, RT stability (SDRT) and confidence (Conf) for each task.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation